Prevalence, O-genotype and Shiga toxin (Stx) 2 subtype of Stx-producing Escherichia coli strains isolated from Argentinean beef cattle - Okuno, Kentaro (2021)
The aims of this study were to investigate prevalence, O-genotype, and virulence gene profile including Shiga toxin 2 gene-subtype of Stx-producing Escherichia coli (STEC) in beef cattle from the Bahía Blanca in Argentina. Rectal swabs were collected from 283 beef cattle in 2012. stx genes were detected in 90 (32%) out of the 283 rectal swabs by stx gene-specific PCR assay. The positive cases were 13 with stx1, 58 with stx2, and 19 with both stx1 and stx2. Among 90 stx gene-positive samples, 45 STEC strains were isolated, which included 3 stx1, 34 stx2, and eight stx1 and stx2 genes positive isolates. O-genotyping grouped 45 STEC strains into 19 different O-genotypes such as Og8, Og145, Og171, Og185 (4 from each) , Og22, Og153, Og157 (3 from each) and others. Various stx2 gene37 subtypes were identified in 42 STEC strains: 13 positive cases for stx2a, 11 for stx2c, 3 for stx2g, 10 for stx2a and stx2d, 4 for stx2a and stx2c, and 1 for stx2b, stx2c and stx2g. efaI gene, generally prevalent in clinical strains, was detected in relatively high in the STEC strains. These data suggest that stx2a and stx2c were distributed not only in O145 and O157 but also in minor O-genotypes of STEC in Argentina.